Traditional Game Learning Models to Develop Student Creativity - Bahtiyar Heru Susanto (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
The purpose of this study is to develop a model of physical education learning through traditional games to develop creativity in elementary school students. This research is designed using the research and development method  in six steps, namely preliminary studies, initial product development, validation and revision, small-scale trials, small-scale trials,  and the final product. This analysis in research and development uses descriptive statistical analysis. The trial subjects were 22 elementary school students. Has a result of research shows that the creativity of elementary school students can be developed through a learning model in which there are traditional games. The aspects of creativity that are measured in students are 4P (Creative person, Press, Creative process, Creative product). The results of filling out the questionnaire that has been carried out by each expert and teacher obtained an overall average of 3.58, so it is included in the good criteria. The results of analysis of field trial data, namely questionnaires for students on learning, obtained an average percentage of the corresponding answers of 89.25%. Based on the criteria that have been set, the product of developing a physical education learning model through traditional games has met the criteria so that it can be used for elementary school students.